المقاومة الثقافية في شعر محمد العيد آل خليفة - حاقة, عبد الكريم (University of Eloued جامعة الوادي, 2022)
منذ أن وطئت أقدام المحتلين أرض الجزائر والشعب يقاوم، تارة بالسلاح، وطورا بالفكر، وقد برزت المقاومة الثقافية مطلع القرن العشرين. وفي هذه الورقة البحثية حاولت الإجابة عن الإشكال الرئيس الآتي: كيف تبلورت المقاومة الثقافية في شعر محمد العيد آل خليفة؟ حيث تمت الإجابة وفق خطة تبدأ بمقدمة وتنتهي بخاتمة، وتتضمن عدة مباحث أهمها المبحث التطبيقي الذي رصدت فيه شعر المقاومة الثقافية عند محمد العيد من خلال ديوانه. وقد توصلت إلى نتيجة هامة هي: أن شعر المقاومة الثقافية كان مبثوثا في ثنايا الديوان لا تكاد تخلو منه قصيدة. Abstract : Since the occupiers set foot on the land of Algeria, the people have been resisting, sometimes with weapons, and sometimes with thought, and cultural resistance has emerged at the beginning of the twentieth century. In this research paper, I tried to answer the following main problem: How did cultural resistance crystallize in the poetry of Muhammad Al-Eid Al Khalifa? Where the answer was carried out according to a plan that begins with an introduction and ends with a conclusion, and includes several topics, the most important of which is the applied topic in which I monitored the poetry of cultural resistance by Muhammad al-Eid through his poetry. And I reached an important conclusion: that the poetry of cultural resistance was spread in the folds of the Diwan, almost devoid of a poem.
Cultural resistance in the poetry of Muhammad Al-Eid Al-Khalifa
مداخلة
Keywords: الشعر؛ المقاومة الثقافية؛ الوطن؛ اللغة العربية؛ الإسلام; Hair; cultural resistance; Motherland; Arabic; Islam